2012
DOI: 10.1136/bmj.e2958
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes in men screened for abdominal aortic aneurysm: prospective cohort study

Abstract: Objective To determine whether there is a relation between aortic diameter and morbidity and mortality in men screened for abdominal aortic aneurysm.Design Prospective cohort study.Setting Highland and Western Isles (a large, sparsely populated area of Scotland).Participants 8146 men aged 65-74. Main outcome measuresMorbidity and mortality in relation to presence of abdominal aortic aneurysm and three categories of aortic diameter (≤24 mm, 25-29 mm, and ≥30 mm).Results When screened, 414 men (5.1%) had an aneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 18 publications
2
22
1
Order By: Relevance
“…The study by Duncan et al was limited by exclusion of women (on the assumption that aortic dilation is more common among men). 22 …”
Section: Discussionmentioning
confidence: 99%
“…The study by Duncan et al was limited by exclusion of women (on the assumption that aortic dilation is more common among men). 22 …”
Section: Discussionmentioning
confidence: 99%
“…24 People with sub-aneurysmal aortic dilatation or AAA are at higher risk of cardiovascular death than those with normal infrarenal aortic diameter. 25 It should also be noted that the relationship between aortic diameter and cardiovascular mortality is not linear and individuals with both small and large aortic diameters are at higher risk of cardiovascular mortality and morbidity. 26 The increased risk in patients with AAA is partly due to common risk factors for both AAA and other cardiovascular traits.…”
Section: Cardiovascular Risk Managementmentioning
confidence: 99%
“…Duncan et al conducted the prospective cohort study of long-term outcomes in men (n ¼ 8146, aged 65-74 years) for AAAs in relation between aortic diameter, morbidity, and mortality. 26 All-cause mortality was significantly associated with aortic diameter: 512 (7.2%) men in the #24-mm group died compared with 69 (10.3%) in the 25-to 29-mm group and 73 (17.6%) in the $30-mm group. The mortality risk in men with an aneurysm or with an aorta measuring 25 to 29 mm was significantly higher than in men with an aorta of #24 mm.…”
mentioning
confidence: 96%
“…Despite the widespread use of diameter measurements in clinical trials and its ease of ascertainment in clinical practice, several studies have also concluded that the diameter may not be reliable as rupture risk criterion and that it should be replaced by a more specific criterion. [27][28][29] Therefore, multiple studies have focused on patient-specific issues such as peak wall stress [25][26][27] or intraluminal thrombus in AAAs. [33][34][35][36] In the current era, these determinants of AAA progression and cardiovascular events are still poorly understood, and thus have proven to have limited clinical applicability over diameter measurement at the present time.…”
mentioning
confidence: 99%